The necessity of drawing up the annual production plan and the importance of establishment crop structure for next agricultural year - Daniela-Elena Șurcă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Planning represents establishment and substantiate the objectives, accomplish tasks and necessary resources for appropriate period plan ( of perspective, annual, quarterly, monthly). Drawing up annual production plan into a ferm is required primarily for evolution or involution recorded by economical phenomenes, which directly determines the operation of the farm. After determining the annual production plan can establish structures and cultures for the next agricultural year using modeling and simulation methods. Following the application of modeling and simulation methods in a farm resulting optimal dimensions of business operations with profit maximization in terms of economic efficiency increased.
Keywords: 330; production plan; resources; technical and economic indicators; modeling and simulation